The Cultural and Intellectual Rebuilding of France After the Second World War - Kelly, M. author. aut Link
X, 232 p.
Keywords: This book reveals how France reinvented itself in the aftermath of World War Two. After foreign military interventions, the French political and intellectual elites embraced regime change and launched an urgent programme of nation building. They rebuilt French national identity with whatever material was available, and created a vibrant new cultural and intellectual life. The cost to subordinated groups, however, especially women, still casts a long shadow over French values and attitudes. In this, perhaps, there are lessons and implications for other countries, struggling to rebuild themselves after conflict.